A Procedural Approach to Judicial Reform in Asia: Implications from Japanese Involvement in Vietnam - Kaneko, Yuka (Columbia Journal of Asian Law, 2010)
This article attempts to bring a civil procedural approach to law and development studies. The focus is on recent judicial reform in Vietnam, where influential international donors have directed the adoption of a set of rigorous reform proposals, including the ihdependence of judicial ad- ministration, an adversarial civil procedure, and the judgment disclosure system, as conditions under compelling frameworks such as the U.S. – Vietnam Trade Agreement and negotiations to enter the WTO. The results were, however, something different from the original American model: strengthened institutional independence of the judiciary increased verti- cal pressure over the adjudicative level; a new civil procedure law that still retained the tradition of social dispute resolution; and the reach of judgment disclosure was limited to the supreme cassation decisions. In this standoff Japanese assistance has been involved with an incremental approach backed by Japan’s own experience of a hundred years’ judicial struggle for adjudicative independence. This article explores the nature of donor-recipient interaction in pursuit of a procedural framework that is actually workable in local contexts, so as to balance the twin needs of integrity and flexibility in applying formal law in a changing society. This procedural approach will start with the recognition of constitutional restraints on adjudicative independence, consider the design of civil procedures both protecting and controlling adjudicative independence, and finally, observe the outcomes of these procedural characteristics in the actual adjudicative process, through the study of cassation cases as well as interviews with judges.